Do sport compression stockings improve comfort and accelerometry parameters in runners? - Oficial, F. J.; Aparicio, I.; Julián, I.; Pérez-Soriano, P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to evaluate the performance of new algorithms based on foot-worn inertial measurement units (IMUs), to detect foot contact time and foot strike angles in running. Treadmill instrumented with force plate and camera-based motion capture system were use as reference system. For 35 participants running on treadmill with different speeds, contact time and foot strike angle values obtained from IMUs were compared with those measured by force plate and motion cameras, respectively, with a relative error (mean ± SD) of -10.5 ± 2.2% and 3.9 ± 5.3°. This error could be further reduced using a corrective model based on the runner`s speed and foot strike angle.